NEUROMARKETING INSIGHTS INTO BRAND LOYALTY FORMATION IN GEN Z CONSUMERS - Loso Judijanto; Dodi Setiawan Riatmaja; Baskoro Ajie (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to explore the role of neuromarketing in understanding the formation of brand loyalty among Generation Z consumers. This generation has unique characteristics, such as a strong attachment to digital technology, a preference for authentic experiences, and a tendency to connect emotionally with brands. Using a literature review method, this study examines the results of previous studies that focused on the application of neuroscience in marketing, specifically in uncovering how visual, emotional, and cognitive stimuli influence Gen Z consumer behavior. The results show that brand loyalty among Gen Z is built not only through product quality and price, but also through emotional resonance, social values, and immersive digital experiences. Neuromarketing, through techniques such as eye-tracking, brainwave analysis, and physiological response measurement, can provide a more accurate understanding of consumers' subconscious preferences that are often not revealed through traditional survey methods. This study confirms that integrating neuromarketing insights with branding strategies can be key to building long-term relationships between brands and Gen Z consumers.